The consumer purchase motivation of Organic Food in Online Retail - Rina Yanti; Wahyudi David; Ardiansyah (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2024)
Organic food relies on consumer confidence as the driver of its buying process. Generally, consumers purchase it directly to ensure its organic guarantee. The increasing purchase of agricultural products and organic food online in Indonesia shows consumer confidence in organic products sold in e-commerce. These studies aimed to determine the driving factors of purchasing organic food through online retailing, the types of organic food purchased, and the relationship between consumer motivation and purchasing decisions. This study uses a cross-sectional method with a purposive sampling technique, and the data is processed using SPSS with General Linear Model analysis. The results from 102 respondents in Indonesia showed that convenience, practicality, and time efficiency as the biggest motivation of consumers (85.30%). On the other hand, pleasure is the slightest consumer motivation (1.0%). Vegetables and processed seeds/nuts are widely purchased as fresh and processed organic foods. The relationship between consumer motivation and online purchasing decisions is that both variables affect one another. The consumer motivation driving factors are diverse product variants, attractive packaging, organic labels, nutritional value, discounts, time efficiency in purchasing, easy-to-find online stores, and advertising. Affordable prices do not motivate consumers to purchase organic food online. Therefore, organic food consumers in Indonesia purchase products through online retailing for convenience.